2018
DOI: 10.1007/s11269-018-2103-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transformative Capacity in River Basin Management Transformations

Abstract: Highlights-Lack of studies analyzing transformative capacity in RBM in a multi-scale setting -We analyzed transformations and transformative capacity in the River Vantaa basin, Finland -Temporal analysis by examining earlier research, policy documents and a stakeholder workshop -Three transformations can be identified that have steadily improved the water quality -Transformations and transformative capacity are in a multidimensional relationship

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In this context, Brodnik and Brown ( 2018 ) aimed at linking agency processes to transformative conditions at a systems level, uncovering three distinct TC building phases and their type of agency: (1) introductory capacity—involves instrumental agency processes that increase the system's willingness for new practices; (2) diffusional capacity—requires influential agency processes that enable free self-organising processes to unfold; and (3) establishment capacity—entails influential agency processes that potentials the institutionalisation of new practices. Focusing on the temporal scale of transformations, Räsänen et al ( 2019 ) found that systems’ TC has a multidimensional relationship across spatial, administrative, and temporal scales, as well as that TC is not static and evolves over time, being context-dependent. In the case of Wolfram ( 2019a ), their study highlighted that understanding the learning processes is essential for building TC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Brodnik and Brown ( 2018 ) aimed at linking agency processes to transformative conditions at a systems level, uncovering three distinct TC building phases and their type of agency: (1) introductory capacity—involves instrumental agency processes that increase the system's willingness for new practices; (2) diffusional capacity—requires influential agency processes that enable free self-organising processes to unfold; and (3) establishment capacity—entails influential agency processes that potentials the institutionalisation of new practices. Focusing on the temporal scale of transformations, Räsänen et al ( 2019 ) found that systems’ TC has a multidimensional relationship across spatial, administrative, and temporal scales, as well as that TC is not static and evolves over time, being context-dependent. In the case of Wolfram ( 2019a ), their study highlighted that understanding the learning processes is essential for building TC.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this fragmentation of TC definitions, the results also enabled us to highlight the similar features and differences of TC in the two fields of knowledge. On the one hand, both fields recognise that TC involves the ability to anticipate and respond to ongoing and future changes, whether they are slow-burning pressures or extreme events (Newton et al 2017 ; Räsänen et al 2019 ; Mehryar et al 2022 ). Essentially, TC refers to the ability to create fundamental changes and involves the potential to establish a new system or way of operating when the existing one becomes untenable or undesirable (Wolfram 2016 ; Brodnik and Brown 2018 ; Manyena et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, as social change is ubiquitous, it is important to pay attention to the temporal scale of the transformation process, especially when designing research approaches. Research approaches that focus on historical developments may yield insights that cannot be captured with more common case study approaches (Räsänen et al , 2019), but may present challenges in data collection. Fourth, the tried-and-tested methods of many disciplines can be used to study sustainability transformations in empirical case studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, imposing collective action and inclusive forms of governance require leadership that can translate visions and global/ national issues into local processes (Räsänen et al, 2019). Consequently, communication of urban transformation should clearly describe the current and future consequences of climate change, as well as how the role of participation is to be tackled, on a scale that makes sense to citizens (Ziervogel, 2019).…”
Section: Envisionmentioning
confidence: 99%